Biotic resources in the Lower Magdalenian at Cova Rosa (Sardeu, Asturias, Cantabrian Spain) - Álvarez-Fernández, Esteban (2019)
Cova Rosa is an archaeological site in Asturias, Spain, excavated by Francisco Jordá Cerdá in 1958, 1959 and 1964. Later, the same archaeologist and Alejandro Gómez Fuentes carried out an excavation from 1975 to 1979. They documented two levels, named Cova Rosa A and Cova Rosa B. The archaeological material resulting from this excavation has remained practically unpublished. This paper presents the biotic remains (ligneous and faunal resources) in Layer B6, dated by radiocarbon to about 15,800 BP (c. 18,700 cal BP), corresponding to the Lower Magdalenian. Anthracological analysis shows that the human groups selected mostly shrub species for their fires. Archaeozoological information indicates that hunting specialising in red deer predominated, while fishing salmonids and shellfishing (mostly limpets and periwinkles) were complementary activities to hunting and gathering plants. Other economic activities practiced in the cave were the fabrication of osseous implements and objects of adornment made with animal raw materials. Through the biotic remains that have been documented, it can be inferred that, at that time in Greenland Stadial 2, conditions were relatively cold and humid, and the vegetation was dominated by grasslands and shrubs.